2007
DOI: 10.1143/jjap.46.2157
|View full text |Cite
|
Sign up to set email alerts
|

Overview and Future Challenge of Ferroelectric Random Access Memory Technologies

Abstract: We have developed a low-temperature formation technique for ferroelectrics (<500 °C), which is crucial for the ferroelectric random access memory (FeRAM) to be embedded in a leading-edge complementary metal oxide semiconductor (CMOS). A 53-nm-thick Bi4Ti3O12 film was successfully formed by metalorganic chemical vapor deposition at 450 °C and subsequent annealing at 500 °C. It was found that perovskite grains preferentially orient along the (110) and (111) directions and that the fabricated Bi4Ti3O12 capacitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…[8][9][10][11][12] Such properties make perovskite oxides very promising for several applications. The potential applications of these materials include ferroelectric random access memory, multilayer ceramic capacitors, magnetic eld sensors, solid oxide fuel cells (SOFCs), membranes, catalytic converters [13][14][15][16][17][18][19][20] etc. Such wide range applications of these materials require us to understand their electrical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Such properties make perovskite oxides very promising for several applications. The potential applications of these materials include ferroelectric random access memory, multilayer ceramic capacitors, magnetic eld sensors, solid oxide fuel cells (SOFCs), membranes, catalytic converters [13][14][15][16][17][18][19][20] etc. Such wide range applications of these materials require us to understand their electrical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…These simultaneous and independent studies concluded the possibility of utilizing antiferroelectric (AF) materials for nonvolatile random access memory (RAM) chips called AFRAM [14]. The AFRAM memories bring considerable improvements to ferroelectric RAM (FRAM) [15][16][17][18][19], while maintaining key features of FRAM such as low power consumption, ultrafast data access times, and read/write endurance of >10 12 . These discoveries and proposed applications can be turned into commercial products only if the temperature, time, and electric field dependence of the polarization dynamics in antiferroelectrics are fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…coverage of narrow 3-dimensional electrode structures [8][9][10], chemical solution deposition (CSD) [11] is a comparatively inexpensive and highly flexible technique which is applied for planar FeRAM cells, actuators and sensors [12]. In particular CSD offers the specific advantage of providing high flexibility with regard to stoichiometric variations including the addition of dopants [13][14][15].…”
Section: While Metal-organic Chemical Vapor Deposition (Mocvd) Is a Kmentioning
confidence: 99%